Near-Native Visualization of SARS-CoV-2 Induced Membrane Remodeling and Virion Morphogenesis - Tim Bergner; Fabian Zech; Maximilian Hirschenberger; Steffen Stenger; Konstantin M. J. Sparrer; Frank Kirchhoff; Clarissa Read (Viruses, 2022)
Infection with the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the causative agent of the COVID-19 pandemic, leads to profound remodeling of cellular membranes, promoting viral replication and virion assembly. A full understanding of this drastic remodeling and the process of virion morphogenesis remains lacking. In this study, we applied room temperature transmission electron microscopy (TEM) and scanning transmission electron microscopy (STEM) tomography to visualize the SARS-CoV-2 replication factory in Vero cells, and present our results in comparison with published cryo-EM studies. We obtained cryo-EM-like clarity of the ultrastructure by employing high-pressure freezing, freeze substitution (HPF-FS) and embedding, allowing room temperature visualization of double-membrane vesicles (DMVs) in a near-native state. In addition, our data illustrate the consecutive stages of virion morphogenesis and reveal that SARS-CoV-2 ribonucleoprotein assembly and membrane curvature occur simultaneously. Finally, we show the tethering of virions to the plasma membrane in 3D, and that accumulations of virus particles lacking spike protein in large vesicles are most likely not a result of defective virion assembly at their membrane. In conclusion, this study puts forward a room-temperature EM technique providing near-native ultrastructural information about SARS-CoV-2 replication, adding to our understanding of the interaction of this pandemic virus with its host cell.